2020
DOI: 10.1002/vms3.347
|View full text |Cite
|
Sign up to set email alerts
|

“Immunolocalization and effect of low concentrations of Insulin like growth factor‐1 (IGF‐1) in the canine ovary”

Abstract: Insulin like growth factor‐1 (IGF‐1) plays an important role in the regulation of ovarian function. Despite its extensive study in several species, there is a paucity of information about IGF‐1`s function and localization in the canine ovary. The aim of the present study was to assess the effect of IGF‐1 on oocyte nuclear maturation and to immunolocalize the IGF‐1 and its receptor (IGF‐1R) in the ovary. Cumulus‐oocyte complexes (COCs) were obtained from 34 bitches. The COCs from each bitch were incubated in TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…It has already been reported that IGF-1 plays an important role in the regulation of ovarian function. A recent study suggested both IGF-1 and IGFR are localized in all ovarian structures including the corpus luteum [ 59 ], and the IGF activity in the ovarian follicle influences follicle development, steroidogenesis and oocyte quality [ 60 ]. The supplementation of IGF-1 to the IVM culture medium improved the IVM and in vitro fertilization rate in porcine oocytes [ 61 ] and this factor stimulates protein kinase A-dependent intracellular mechanisms that involved both meiosis and completion of oocyte nuclear maturation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has already been reported that IGF-1 plays an important role in the regulation of ovarian function. A recent study suggested both IGF-1 and IGFR are localized in all ovarian structures including the corpus luteum [ 59 ], and the IGF activity in the ovarian follicle influences follicle development, steroidogenesis and oocyte quality [ 60 ]. The supplementation of IGF-1 to the IVM culture medium improved the IVM and in vitro fertilization rate in porcine oocytes [ 61 ] and this factor stimulates protein kinase A-dependent intracellular mechanisms that involved both meiosis and completion of oocyte nuclear maturation [ 62 ].…”
Section: Discussionmentioning
confidence: 99%